Preparation, Characterization and In Vitro Biological Evaluation of Novel Curcumin Derivatives as Cytotoxic and Apoptosis-Inducing Agents - Arjomandi, Omid K.; Almasi, Saiedeh; Hosseinzadeh, Leila; Kavoosi, Mahboubeh; Adibi, Hadi (Anti-Cancer Agents in Medicinal Chemistry, 2021)
Background: Curcumin is a natural polyphenol and lead compound of the rhizomes of curcuma longa and it has been widely used for pharmacological activities. Objective: In this study, a series of novel derivatives of curcumin, with this group linked to a 2-amino-4- phenylpyran-3-carbonitrile system, have been synthesized and tested for their antitumor activities in vitro against a panel of three human cancer cell lines (MCF-7, A2780, and U-87MG). Methods: The in vitro cytotoxic activity of the synthesized compounds was tested on three cancer cell lines (MCF-7, A2780, and U-87MG) using MTT colorimetric assay. Meanwhile, the ability of the active compounds to induce apoptosis in cancer cells was investigated by examination of caspase-3 and caspase-9 and mitochondrial membrane potential assay. Results: Under relatively mild conditions in ethanol, the reaction of a series of substrates afforded the corresponding derivatives of curcumin mostly in good yields (13 analogues, 48-94% yields). Bioassay results indicated that compounds L6 (para-Bromo), L9 (para-Nitro) and L12 (meta-Methoxy) were the most active members in this study demonstrating potent activities against A2780 cancer cells and experimental results of fluorescent staining and flow cytometry analysis revealed that L6 and L9 could induce apoptosis in A2780 cells with apoptosis ratios of about 40% and 46%, respectively at 24h of treatment at 15.35μM and 23μM in A2780 cells. On the other hand, they could increase the caspase-3 activity slightly (10%), while having no significant impact on the activities of caspase-9. Conclusion: Those two derivatives could be considered as useful templates for future development to obtain more potent antitumor agents.
Keywords: cytotoxicity tests